2015
DOI: 10.1111/fare.12159
|View full text |Cite
|
Sign up to set email alerts
|

Role of Institutional Climate on Underrepresented Faculty Perceptions and Decision Making in Use of Work–Family Policies

Abstract: The authors examined the institutional challenges that underrepresented minority (URM) faculty perceive in higher education with use of family support workplace policies. Evidence reveals that faculty encounter differences in access to information and explanations of how to use workplace–family statutes. A qualitative study of 58 URM faculty members highlighted five particularly notable themes: (a) faculty perceptions of how the institution views their family caregiving responsibilities, (b) inadequate compens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
(39 reference statements)
1
8
0
Order By: Relevance
“…Family life outside the workplace bears weight in understanding vocational strains and overload. URM professionals often have larger families, more family obligations, a fear of using family leave policies, additional household time demands, and a ‘wealth gap’ that disallows the outsourcing of domestic services (Castañeda et al, 2015; Hamilton & Darity, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Family life outside the workplace bears weight in understanding vocational strains and overload. URM professionals often have larger families, more family obligations, a fear of using family leave policies, additional household time demands, and a ‘wealth gap’ that disallows the outsourcing of domestic services (Castañeda et al, 2015; Hamilton & Darity, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For most participants, economic strain was paramount in their lives as neither they nor their parents were financially secure enough to supplement financial resources outside of their own salaries and savings. Respondents reported frequently confronting economic and institutional social support hurdles that hinder the pursuit of balancing family, work, and personal selves (Castañeda et al, 2015). For example, work settings that provide leave for childbirth or illness frequently do not cover a full-semester salary.…”
Section: Outflow Of Resources: Commitments and Burden Of Family Of Or...mentioning
confidence: 99%
“…This combination of scrutiny and underappreciation creates a unique set of challenges for faculty parents of color, potentially leading to heightened pressure to adhere to the ideal-worker norm, conceal family issues, and under-utilize family-friendly policies. Indeed, faculty members of color report concerns about using such policies ranging from worries about how their parenting responsibilities will be viewed to salary inequities making use of policies cost prohibitive (Castañeda et al, 2015). Along these lines, Settles et al (2019) found that one response of faculty of color to heightened scrutiny was to work even harder, taking on extra work to prove themselves.…”
Section: Race/ethnicitymentioning
confidence: 99%